A Non-Verbal Communication of Jack Mc Call on A Thousand Words Movie - Ismawati, Krisna; Ira Maisarah (Journal of English for Specific Purposes in Indonesia, 2024)
Individuals interact through two components, namely verbal and nonverbal communication. The two components are inseparable. This article aims to examine the nonverbal cues exhibited by the American character, Jack Mc. Call, portrayed in the film "A Thousand Words". This is a high-quality document. It contains two categories of information. The primary data is obtained from the film's screen captures that emphasize Jack's nonverbal cues. The supporting data encompass additional information that bolsters the examination. The method employed for gathering data involves conducting research at the library and utilizing the subsequent procedures: viewing the film and capturing screenshots of the scenes that pertain to Jack's nonverbal communication. Analyzing data is executed by utilizing the principles of nonverbal communication. Initially, the American way of communication is distinctly dissimilar from the Asian approach, which often involves showing respect by bowing during conversations. Secondly, as Americans speak more attentively, they frequently rely on gestures and facial expressions, as mentioned previously. Jack represents American nonverbal communication.